Utilization of the Mobile Library Application via Smartphone - Adzkiyah Mubarokah; Heni Nopianti; Fransiska Timoria Samosir (Record and Library Journal, 2023)
Background of the study: The use of technology in an all-digital world has made the Lubuklinggau City Library and Archives Service innovate to create a mobile library named Ilubuklinggau. Purpose: This study examines the use of the Ilubuklinggau mobile library application through a smartphone. This study aims to determine the use of existing collections in Ilubuklinggau by users, to find out the fulfillment of digital collection needs in the Ilubuklinggau application, and to know the skills of the community in accessing information through the Ilubuklinggau mobile library. Method: The research method used is a qualitative approach. The research subjects were 6 people consisting of 3 users of the Ilubuklinggau application and 3 library staff, informants as data sources were taken with certain considerations. Findings: Utilization is explained using the Unified Theory of Acceptance and Use of Technology (UTAUT) model parameters. Based on this research, it is concluded that the results of 4 aspects include: 1) aspects of performance expectations 2) business expectations 3) social influences 4) facilitation conditions. These four aspects must be possessed in order to make optimal use of the Ilubuklinggau mobile library application through smartphones. Conclusion: The Ilubuklinggau application helps performance and makes it easier in terms of use, as well as increasing the competence and existence of the library, but this application has several obstacles that affect utilization such as incomplete collections due to budget conditions and face-to-face socialization that has not been held so that application enthusiasts are still lacking.